Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, dan Pertumbuhan Aset Terhadap Nilai Perusahaan - Putri, Melinda Risqi Setya; Hermuningsih, Sri; Wiyono, Gendro (Politeknik Ganesha Medan, 2024)
This research aims to examine the influence of Profitability, Leverage, Company Size, and Asset Growth as independent variables on Company Value as the dependent variable. Profitability is measured by Return On Assets, Leverage is measured by Debt Ratio, company size is measured by Ln total assets, asset growth is measured by asset growth, and company value is measured by Price to Book Value. This research is quantitative research. The sample in this research was obtained using a purposive sampling method, namely selecting samples using predetermined criteria. Based on the purposive sampling method with predetermined criteria, 105 samples were obtained from 21 property and real estate sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The analytical method used is descriptive statistical analysis, classical assumption tests which include normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests, as well as multiple linear regression analysis and hypothesis testing used is the coefficient of determination test (R square), F-test and test. -t which was processed using the SPSS version 26 program. The research results show that profitability has a positive and significant effect on company value, leverage has no significant effect on company value, company size has a positive and significant effect on company value, asset growth has no significant effect on company value.